Study on Male Breast Cancer (Journal of Chittagong Medical College Teachers' Association, 2021)
Background : Male Breast Cancer (MBC) is a rare disease all over the world accounting for less than 1% of all breast cancers. Histopathologically most of the cases are infiltrating ductal carcinoma. Treatment depends on the stage and biological behavior like ER, PR and HER-2 status of the disease, general condition and other comorbidities of the patient. Like female breast cancer, different modalities like surgery, chemotherapy, radiotherapy, hormone therapy, immunotherapy and targeted therapy are the mainstay of treatment. This analytical study was carried out to see the clinical and biological behavior, risk factors and treatment pattern of the disease.Materials and methods: This analytical study was carried out in the Department of Radiotherapy, Chittagong Medical College Hospital and Centre for Specialized Care and Research Hospital, Chattogram from January 2005 to July 2020. Total 28 numbers of patients of postoperative breast cancer were enrolled in the study. Case records including follow up records were collected for all cases. Clinical, histopathological and molecular biomarker data were analyzed.Results: Majority of the patients (20 in number, 71.43%) belonged to age group 51-70 years. 23 patients (82.14%) were smoker. 19 patients (67.8%) had lump in the left breast. Infiltrating duct cell carcinoma was the dominant histopathological type. More than 90% cases were of this type of histopathology. All the cases presented with axillary lymph node metastases. One patient had second malignancy who was previously diagnosed and treated as a case of lung cancer. Two patients had positive family history of breast cancer.Conclusion: As a rare disease, sample size was very small in this study. Comprehensive multi center studies are needed to better understand this disease.JCMCTA 2021 ; 32 (1) : 35-39